Geospatial Modeling of the Nitrate Distribution as an Indicator of Aquatic Fertility in the Lagoon Waters of the Mangrove Information Center (PIM), Pekalongan - Zainuri, Muhammad; Suryani, Oda Gracia Ariela; Ismanto, Aris; Handoyo, Gentur; Rifai, Azis; Rochaddi, Baskoro; Endrawati, Hadi; Kusumaningrum, Hermin Pancasakti; Jihadi, Muhammad Shulhan; Hadibarata, Tony (Universitas Diponegoro, 2024)
In the lagoon area of the Mangrove Information Center (PIM), Pekalongan, annual flooding leads to inundation in some land areas, particularly pond areas, lagoons, and residential areas. The area of submergence due to tidal floods in 2020 reached 783.99 hectares. The construction of embankments to the south of the lagoon as protection against flooding has transformed the northern area into a lagoon. Our research, crucial for understanding and managing these environmental changes, aims to determine and analyze the content and distribution of nitrate in the Lagoon Area of Mangrove Information Center Waters, Pekalongan. This was achieved through a thorough process of in situ observations based on purposive sampling at six sampling sites on June 22, 2023. The nitrate distribution data was then interpolated with a 2D current hydrodynamic model, ensuring the most accurate representation of the data. The value of nitrate content in the Mangrove Information Center lagoon ranges between 0.0065-0.1072 mg/L. This distribution pattern, influenced by deposits of mangrove litter, the depth of the lagoon, and water circulation, reflects the accumulation of physical and chemical influences in the waters.